2009
DOI: 10.1111/j.1600-0722.2009.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of orthodontic tooth movement by experimentally induced periodontal inflammation in mice

Abstract: Orthodontic therapy is known to have an aggravating effect on the progression of destructive periodontitis if oral hygiene is not maintained. However, it is largely unknown how active periodontitis affects the velocity of orthodontic tooth movement. In this study, we examined the effect of periodontal inflammation on orthodontic tooth movement using a mouse model. Orthodontic force was applied on the maxillary first molar of mice, with or without ligature wire to induce experimental periodontitis. The distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 42 publications
(54 reference statements)
1
21
0
1
Order By: Relevance
“…However, a few in-vitro studies involving different cell types have demonstrated that biomechanical forces also exert anti-inflammatory effects [1,18,19]. Interestingly, the relationship between orthodontic treatment and periodontitis seems to be bidirectional because periodontal inflammation may also affect the velocity of orthodontic tooth movement, as it has been suggested in a recent study in mice [20]. In addition to inflammatory mediators, the homeostasis of periodontal tissues is also affected by growth factors, such as insulin-like growth factor (IGF) 1, transforming growth factor (TGF) β1, and vascular endothelial growth factor (VEGF), which promote cell proliferation, differentiation, migration, and synthesis of extracellular matrix molecules, such as collagen type I (COL1) [6].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, a few in-vitro studies involving different cell types have demonstrated that biomechanical forces also exert anti-inflammatory effects [1,18,19]. Interestingly, the relationship between orthodontic treatment and periodontitis seems to be bidirectional because periodontal inflammation may also affect the velocity of orthodontic tooth movement, as it has been suggested in a recent study in mice [20]. In addition to inflammatory mediators, the homeostasis of periodontal tissues is also affected by growth factors, such as insulin-like growth factor (IGF) 1, transforming growth factor (TGF) β1, and vascular endothelial growth factor (VEGF), which promote cell proliferation, differentiation, migration, and synthesis of extracellular matrix molecules, such as collagen type I (COL1) [6].…”
Section: Introductionmentioning
confidence: 84%
“…Einige In-vitro-Untersuchungen an verschiedenen Zelltypen haben gezeigt, dass biomechanische Kräfte auch antiinflammatorische Effekte ausüben [1,18,19]. Interessanterweise scheint die Beziehung zwischen kieferorthopädischer Zahnbewegung und Parodontitis bidirektional zu sein, da eine Parodontitis auch die Geschwindigkeit der kieferorthopädischen Zahnbewegung beeinflussen kann, wie eine kürzlich veröffentlichte Studie an Mäusen nahelegt [20]. Neben Entzündungsmediatoren wird die Homöostase des Parodonts auch durch Wachstumsfaktoren wie z.B.…”
Section: Introductionunclassified
“…However, the comprehensive relationship among periodontitis, tobacco smoking, and orthodontic tooth movement is clinically yet to be explored. The feasibility of orthodontic treatment is still controversial for adult patients with destructive periodontal diseases [21]. Thus, we firstly attempted to evaluate the effects of TSCs on mechanical force-induced bone resorption at the middle of the alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, OM did not accelerate periodontal breakdown on teeth with supra‐osseous periodontal lesions 19 . In addition, periodontal disease may act to reduce orthodontic tooth movement, as has been shown in mice 21 …”
mentioning
confidence: 84%